Pengembangan Media Video Animasi berbasis Canva Materi Rantai Makanan Siswa Kelas V SD Negeri 1 Moyoketen - Eka Ratna Pramudita; Ria Fajrin Rizqy Ana (Jurnal Simki Postgraduate, 2024)
This research aims to describe the process of developing, testing the validity and applicability of Canva-based animated video media for class V food chain material at SD Negeri I Moyoketen. This research uses the ADDIE development model including analysis, design, development, implementation and evaluation. This data collection technique was carried out using questionnaires and documentation. The instrument used was a questionnaire validation sheet for media experts, material experts, student responses and teacher responses. The results obtained, media expert I questionnaire validation obtained 95% with a very valid category, media expert II obtained 95% with a very valid category, material expert I obtained 90% with a very valid category, material expert II obtained 95% with a very valid category. The results of the applicability of student responses were 88.5% in the very valid category and the results of the applicability of teacher responses were 90% in the very valid category. The results of this research can be concluded that "Food Chain Material Animated Video Media for class V SD Negeri I Moyoketen" is very valid to use and can be applied to learning at SD Negeri I Moyoketen and makes learning more enjoyable by using learning media.